To Catch a Predator - Adler, Amy (Columbia Journal of Gender and Law, 2011)
In the last two decades, a new term-“sexual predator”- has arisen to describe criminals who commit sexual offenses against children. We used to refer to such offenders as “pedophiles” or perhaps “child molesters.” Since this new terminology first emerged in the 1990’s, the word “predator” has become a term of art in legal regulation, and a mainstay in media reports and in the popular imagination. How did the “pedophile” become the “predator”? And what were the effects of this transformation? As the category took shape, a vast new legal apparatus arose to regulate and monitor this emerging species of criminal. New methods developed4 to detect and scrutinize him. The term “predator” implied that the offender was relentless and animal- like; thus, it no longer sufficed merely to send him to jail. After his release, we now had to register him, track him for the rest of his life, or commit him indefinitely to a mental hospital. Some states began to castrate him. Since the term “predator” first emerged, its meaning has expanded and mutated to include a broadening array of sex criminals. The category now encompasses a diverse range of offenders, from the most violent child rapists to teens who possess “child pornography (a term that has an extremely expansive. definition in its own right).”